2021
DOI: 10.1186/s12985-021-01543-x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of an enzymatic assay for rapid measurement of antiretroviral drug concentrations

Abstract: Objective Maintaining adequate drug adherence is crucial to ensure the HIV prevention benefits of pre-exposure prophylaxis (PrEP). We developed an enzymatic assay for rapidly measuring tenofovir-diphosphate (TFV-DP) concentrations—a metabolite that indicates long-term PrEP adherence. Setting The study was conducted at the Madison HIV Clinic at Harborview Medical Center in Seattle. Methods We enrolled a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…We previously demonstrated that we could achieve a CV of 13.5% when running RESTRICT with whole blood samples diluted in water. 30 , 31 Improvements in sample preparation—incorporating a heating step after blood dilution to denature blood proteins (e.g., hemoglobin) that nonspecifically inhibit reverse transcriptase 46 —have improved the accuracy even further (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that we could achieve a CV of 13.5% when running RESTRICT with whole blood samples diluted in water. 30 , 31 Improvements in sample preparation—incorporating a heating step after blood dilution to denature blood proteins (e.g., hemoglobin) that nonspecifically inhibit reverse transcriptase 46 —have improved the accuracy even further (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any significant deviation from expected RESTRICT assay performance in our pilot evaluation study with 18 clinical samples. 31 This is likely because dNTP concentrations in red blood cells and plasma are too low to effectively compete with nucleotide analogs for incorporation into complementary DNA strands synthesized by HIV RT. Our inclusion of a 10‐fold blood dilution step—to reduce non‐specific enzyme inhibition by blood components—further reduces these already low dNTP concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group reported on an enzymatic assay, termed REverSe TRanscrIptase Chain Termination (RESTRICT), that measures DNA duplex production by reverse transcriptase in the presence of NRTI drugs. 45,46 The assay accurately distinguished TFV-DP drug levels within the clinical range for adherence and has the potential to be a useful test to identify patients with poor adherence to ART and PrEP. 45 Real-time PCR has also been used to quantify inhibitory concentrations of NRTIs in drug development against HIV-1 RT.…”
Section: Introductionmentioning
confidence: 99%